Characterization of mass transfer during membrane filtration processes using novel techniques - Gao, Yi Ben (2015)
Membrane-based separation processes have broad applications in water and wastewater treatment, seawater desalination, food processing, ultrapure water production and energy harvest. However, the efficiency of both osmotically driven (e.g., forward osmosis, FO) and pressure-driven (e.g., reverse osmosis, RO) filtration processes are adversely affected by the coupled phenomena of concentration polarization (CP) and membrane fouling. The concentration build-up in the vicinity of the membrane surface is commonly known as the external CP (ECP) that is greatly affected by the fluid hydrodynamics. On the other hand, the solute accumulation in the porous support layer of the membrane is known as the internal CP (ICP) which is unique in the osmotically driven membrane processes such as FO. ICP is closely associated with the physical properties of the substrate and is usually characterized by the structural parameter, the S value. To mitigate the negative influence of CPs and membrane fouling requires in-depth understanding of the mechanisms of mass transfers during filtration processes, which necessitates the development of novel techniques to visualize and quantify the dynamic physico-chemical processes associated with the membrane filtrations. In this study various novel techniques were exploited to characterize the mass transfers during membrane processes. New experimental protocols were established based on the theoretical models to directly and independently characterize ICP and ECP. In particular, three methods were proposed in an RO mode to evaluate the S value. The Jv-method (water flux), the Rs-method (solute rejection) and the Rt-method (trace contaminant rejection) were realized based on the measurements of the RO permeate flux, solute rejection (e.g., NaCl) and trace contaminant rejection (e.g., boron), respectively. S values determined from the aforementioned methods were compared with that obtained by the conventional FO water flux fitting method. In particular, the Rs-method was recommended. By this approach it was able to determine the solute permeability graphically. It was also feasible to resolve the effect of ECP from that of ICP interpretively using the Rs-method. To investigate the subtle interplay between various membrane substrate structures and ICP, an electrochemical impedance spectroscopy (EIS) system was modified to accommodate the FO processes. The effect of various support structures on CPs was systematically investigated. In particular, three commercial FO membranes with distinct substrate structures were characterized by an EIS incorporated FO system and the impedance spectra were analyzed based on their equivalent circuits. Both static (without osmosis) and dynamic (with osmosis) tests were implemented. In the static tests the limit behaviors of the impedance spectra were employed to resolve the FO membrane structural information from the electrolyte background which was further compared with the scanning electron microscopic micrographs. The dynamic tests under both membrane orientations were conducted to verify the feasibility of using the EIS technique to capture the variation of the developed concentration profiles within the FO substructures. Furthermore, to visualize and quantify the dynamic processes during the membrane filtration (i.e., to study the CP by visualizing the fluid hydrodynamics in the proximity to the membrane surface and to investigate membrane fouling by direct observation of foulant deposition and formation), the optical coherence tomography (OCT) technique was exploited. The Doppler OCT facility incorporated with a cross-flow cell first was employed to characterize the hydrodynamics in a spacer-filled channel. The velocity profile normal to the membrane surface was successfully visualized which is difficult to characterize using conventional membrane characterization techniques. Various flow patterns were generated by varying the spacer orientations with respect to the bulk flow direction. A series of Doppler images was used to reveal the subtle interactions between the fluid and the spacer filaments. The characterization results obtained thereby were used to interpret the performance variation of an RO process with the same spacer configurations. The feasibility of using the Doppler OCT technique to characterize the hydrodynamics of the fluid in a spacer-filled channel was validated by the experimental results. The OCT technique was further exploited to visualize and quantify the growth of a foulant layer during a filtration process. In particular, an OCT system was incorporated with a lab-scale membrane filtration system, and the growth of a fouling layer was observed by using the structural OCT imaging. Taking advantage of the Doppler effects, the OCT-based characterization also provided the velocity profiles of the fluid fields, which is of great value in analyzing the fouling layer formation. The characterization results clearly reveal for the first time the evolution of the morphology of the cake layer under different micro-hydrodynamic environments. This study demonstrates that the OCT-based characterization is a powerful tool for investigating the dynamic processes during membrane fouling.